Paciente masculino de 75 años de edad con diagnóstico de enfermedad pulmonar obstructiva crónica. - Ezeta Acosta, Sarita Eloisa (2021)
Through this work, everything that concerns chronic obstructive pulmonary disease (COPD), its etiology, pathophysiology, risk factors, clinical picture, diagnosis and its treatment will be revealed. Once this work was completed, we realized how important respiratory therapists are in these patients. COPD is a disease that worries health organizations due to its high mortality rate worldwide, in our country the Ministry of Public Health (MSP) has promoted campaigns such as that of Ecuador free of tobacco smoke that aims to prevent the high number of COPD patients. At the conclusion of this study in a clinical case, it was concluded that smoking is the main risk factor for contracting this disease, that is why the basis of treatment is to stop smoking, in order to complement it with treatment pharmacological. Since this pathology has no cure, but adequate and timely control will avoid complications in the patient's health.